2014
DOI: 10.1177/0954405414527955
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model to predict material removal rate during electric discharge machining of cryogenically treated titanium alloys

Abstract: Three grades of titanium alloy Ti (grade 2), Ti-6Al-4V (grade 5) and Ti-5Al-2.5Sn (grade 6) were machined using electric discharge machining after deep and shallow cryogenic treatment. The peak current was observed to be the most significant factor followed by electrode material and pulse-on time. Subsequently, a mathematical model for predicting material removal rate of titanium alloys was developed using dimensional analysis based on the significant process parameters affecting material removal rate and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Especially, A number of researches observed that during the EDM process make it a high potential technology for application in the field of surface modification. 3,4 EDM surface modification is one of the non-conventional surface strengthening techniques, which harden materials surfaces by applying high energy density electrical discharge, it will bring substantial economic benefits to the industry. 5,6 The working process can be divided into four stages:…”
Section: Introductionmentioning
confidence: 99%
“…Especially, A number of researches observed that during the EDM process make it a high potential technology for application in the field of surface modification. 3,4 EDM surface modification is one of the non-conventional surface strengthening techniques, which harden materials surfaces by applying high energy density electrical discharge, it will bring substantial economic benefits to the industry. 5,6 The working process can be divided into four stages:…”
Section: Introductionmentioning
confidence: 99%
“…Copper, copper–chromium, and copper–tungsten electrodes were used to get a comprehensive insight into the cryogenic treatments impact. Marginal improvement of MRR was observed [139].…”
Section: Cryogenic Application In Manufacturing Engineeringmentioning
confidence: 99%
“…Parameters that are likely to affect SR and also cause surface changes on the recast layers were identified using a study from the reported results in the literature [1,4,3]. Three repetitions for each surface roughness measurement were conducted.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…Investigate the effects of cooling time due to pulse off time as prime factor, and peak current intensity as a second factor, of fine machining without using other cooling options, like cryogenically treatment before or in time of processing [1] which provided smooth surface appearance, the cold effect is provided only from the speed and direction of dielectric fluid in the gap area. Regardless of pulse on time which is one of the main factors in MRR (Material Remove Rate), the surface roughness quality is based on efficiency of recasting time of layers [3].…”
Section: Introductionmentioning
confidence: 99%